Ресурси та можливості розвитку екотуризму в Чернівецькому районі Чернівецької області - Бучко, Жанна; Яромій, Олег (Карпатський національний природний парк, 2025)
The resource base for organizing ecotourism in the Chernivtsi district of the Chernivtsi region was studied. Opportunities and ecotourism routes were analyzed with a description of their geographical distribution and operating facilities. Problems and shortcomings of organizing ecotourism activities in the region have been identified.
Resources and opportunities for ecotourism development in Chernivtsi district of Chernivtsi region
Keywords: екотуризм; природно-заповідний фонд; екологічна стежка; туристична діяльність